Analysis of judokas performances at the Tokyo 2020 Olympic Games by age - Chobotko, M.; Chobotko, I. (Scientific Journal National Pedagogical Dragomanov University, 2023)
The article is devoted to the analysis of the age of elite judokas when they reach peak form and its influence on the results in competitions. The study is based on the data of athletes who took part in the Tokyo 2020 Olympic Games. The overall average age of the judokas participating in the competition was 27 years. A comparison of the data showed that 91 athletes were younger than the average age (45%), while 110 athletes were older than the average age (55%). There is a trend that 10% more older athletes were selected for the 2020 Olympic Games than younger ones. With a focus on athletes aged 20 to 36 years, it was found that the peak age of elite judokas is 27 years. Younger judokas, compared to the average age, won bouts with a duration of approximately 6 minutes and 25 seconds, while older judokas won with a duration of approximately 7 minutes and 02 seconds. The data analysis also shows that the functional capabilities of athletes decline with age. These findings help to take into account age as an important factor in the selection of talented judokas and optimise training programmes for athletes of different age groups, contributing to improved performance in competitions.